Genome-wide characterization of NAC transcription factors in Camellia sinensis and the involvement of CsNAC28 in drought tolerance - Zhang, Xueying; Li, Linying; Lang, Zhuoliang; Li, Da; He, Yuqing; Zhao, Yao; Tao, Han; Wei, Jiqian; Li, Qingsheng; Hong, Gaojie (Frontiers in Plant Science, 2022)
ABSTRACT The NAM, ATAF1/2, and CUC2 (NAC) transcription factors, which are members of a plant-specific gene family, play critical roles during the growth and development of plants and in their adaption to environmental stress. Few NAC transcription factors have been functionally characterized in tea plants (Camellia sinensis). Based on the analysis of the gene structure, motif pattern, and evolutionary relationship, we identified 104 NAC genes in C. sinensis. Among them, CsNAC28 is constitutively expressed in all organs, and most significantly, exhibiting remarkable responsiveness to abscisic acid (ABA) treatment and drought stress. ABA is a primary stress-related hormone. Recently, ABA-responsive element binding factor 2 (CsABF2) was identified in the ABA pathway of C. sinensis. However, the involvement of the CsABF2-mediated ABA pathway in regulating CsNACs was not known. Herein, a series of biochemical and genetic approaches supported the fact that CsNAC28 could potentially act as a transcription factor in the downstream of CsABF2. Furthermore, we investigated the function of CsNAC28 in the adapting of a plant to drought stress. The results showed that overexpression of CsNAC28 in Arabidopsis conferred hypersensitivity to ABA treatment and decreased the accumulation of reactive oxygen species (ROS), resulting in improved dehydration tolerance. Under conditions of drought, the expression levels of ABA pathway-related genes and drought stress‒inducible genes were greater in CsNAC28 overexpression lines than in the wild type. Our study’s comprehensive characterization of NAC genes in C. sinensis could serve as a foundation for exploring the molecular mechanism of CsNAC-mediated drought responsiveness.